Multi-stakeholder forums and the promise of more equitable and sustainable land and resource use: perspectives from Brazil, Ethiopia, Indonesia, and Peru - Sarmiento Barletti, J.P.; Larson, A.M. (Commonwealth Forestry Association, 2021)
Multi-stakeholder forums (MSFs) have become a popular mechanism in global development and conservation circles, given the urgency to find transformative approaches to address climate change and unsustainable development. In this current context, it is important to take stock of MSFs, an example of a participatory mechanism that is emerging as a new ‘solution’. The papers in this Special Issue of the International Forestry Review derive from a multi-country comparative research project carried out by the Center for International Forestry Research (CIFOR) that aimed to understand how best to support MSFs organised for more sustainable land and resource use. The seven papers assess the potential of MSFs for more equitable decision-making in regard to land and resource use sustainability, and engage with scholarly debates over these forms of participation. The papers approach MSFs from different theoretical perspectives and analytical interests, yet all engage with issues that stem from the power inequalities that are inherent to these forums. The papers provide more evidence – and a warning – that to get closer to transformational change, we need MSFs that do more than simply bring people to the table.